Advances and challenges in the application of prophylactic hyperthermic intraperitoneal chemotherapy for gastric cancer - Liu, Muyang; Shen, Xiaojun (Frontiers in Oncology, 2026)
Gastric cancer is the fifth most common malignant tumor worldwide and the third leading cause of cancer-related deaths, posing a serious threat to global public health. Despite notable advancements in surgical techniques, systemic chemotherapy, targeted therapy, and immunotherapy in recent years, the overall prognosis for patients with locally advanced gastric cancer (AGC) remains suboptimal, primarily due to the high propensity for local and distant metastasis. Peritoneal metastasis (PM), in particular, has become one of the most formidable clinical challenges owing to its high incidence, inherent resistance to systemic chemotherapy, and extremely poor prognosis. To address this challenge, Prophylactic Hyperthermic Intraperitoneal Chemotherapy (P-HIPEC) has emerged as a focal point of research. This therapeutic modality aims to eradicate microscopic residual tumors and free cancer cells in the abdominal cavity following radical gastrectomy, thereby effectively reducing the risk of peritoneal metastasis and improving long-term patient survival. This review systematically examines the latest research progress of P-HIPEC in the treatment of gastric cancer, provides an in-depth analysis of its mechanism of action, indications, criteria for patient and drug selection, evidence of clinical efficacy, safety controversies, and challenges in standardization. It also looks forward to future research directions in this field, with the aim of providing a valuable reference for clinical practice and academic research.